2012
DOI: 10.1176/appi.ap.10080126
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry in the Harvard Medical School–Cambridge Integrated Clerkship: An Innovative, Year-Long Program

Abstract: Longitudinal integrated clerkship experiences are effective and sustainable; they offer particular strengths and opportunities for psychiatry education, and may influence student choice of specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Students reported feeling empowered to be self-directed learners and critical thinkers 88,131,133,168,194 , increased understanding of relevance of knowledge to career 52,76,102,131,150,190 , increased confidence 70,93,107,131,138,141,161 and motivation 76 . Those studies with level 3 outcomes indicated positive changes in improved communication skills 151 , greater uptake of specialty 121 and improved performance in clinical placements 172 . Some negative perceptions and disadvantages were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Students reported feeling empowered to be self-directed learners and critical thinkers 88,131,133,168,194 , increased understanding of relevance of knowledge to career 52,76,102,131,150,190 , increased confidence 70,93,107,131,138,141,161 and motivation 76 . Those studies with level 3 outcomes indicated positive changes in improved communication skills 151 , greater uptake of specialty 121 and improved performance in clinical placements 172 . Some negative perceptions and disadvantages were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…There were 19 codes under the theme "shortage of educational resources of AMC." Subthemes derived from these codes were as follows: shortage of administrative staff to assist with LIC implementation [23,35,37]; inadequate preceptors to teach students in LICs [18,23,35]; students were unable to meet various types of patients because of their preceptors' subspecialties [23,35]; limited space in hospitals for LIC [22,23,29,38,40,41]; LICs required significant financial resources [23,27,37]; and students' schedules it were complicated to make [18,23,25,35]; and students had to move long distances on a tight schedule [18,23].…”
Section: ) Shortage Of Educational Resources Of Amcmentioning
confidence: 99%
“…A serious limitation in the traditional teaching of psychodynamics in medical schools is that psychotherapy proper is a longitudinal experience, while almost all core clerkships in psychiatry provide only a crosssectional experience. However, a number of innovative programs in recent years have redesigned the psychiatry clerkship as a longitudinal experience (Boyd 2008;Griswold et al 2012). These programs, which are set in outpatient clinics, offer several benefits.…”
Section: Formats For Teaching About Psychotherapy and Psychotherapeutic Interventionsmentioning
confidence: 99%